Advances in librarianship. Vol. 15 - Godden, Irene P., 1932- (Emerald, 1991)
Advances in librarianship is one of the most useful reference sources for developments in the field of libraries and library science. All areas of public, college, university, primary and secondary schools, and special libraries are given up-to-date, critical analysis by contributors who are themselves engaged in the practice of librarianship, in teaching, and in research.
Includes index.
Keywords: Library science.; Information science.; elektronické knihy; electronic books